Sulinggih dalam Pusaran Kuasa: Dukungan Griya Agung Bangkasa kepada Koster-Ace pada Pemilihan Gubernur Bali 2018 - Nugraha, I Putu Ari; Erawan, I Ketut Putra; Pramana, Gede Indra (Jurnal Nawala Politika, 2021)
This study aims to determine factors that can explain Ida Sinuhun Siwa Putra Parama Daksa Manuaba's support for Koster-Ace in the Bali Governor Election 2018. Furthermore, the research is framed using Rational Choice theory of James S. Coleman and Social Capital theory from Robert D. Putnam. The research method used is descriptive qualitative research with primary and secondary data, because it describes factors that led to provision of support by Ida Sinuhun Siwa Putra Parama Daksa Manuaba in the Bali Governor Election 2018. The results of this study are: first, there is a rational choice from Ida Sinuhun Siwa Putra Parama Daksa Manuaba who has calculated profits and losses to achieve the desired goals in supporting Koster-Ace. Second, social capital in the form of longstanding friendships between Ida Sinuhun Siwa Putra Parama Daksa Manuaba and Tjok Ace is another factor in providing support in the Bali Governor Election 2018.   Keywords: Ida Sinuhun Siwa Putra Parama Daksa Manuaba, Rational Choice, Social Capital, Bali Governor Election 2018